Unappreciated Roles for K+ Channels in Bacterial Physiology. Issue 10 (October 2021) - Beagle, Sarah D.; Lockless, Steve W.
Abstract : Potassium (K + ) channels are highly conserved proteins found in all domains of life, that allow for selective movement of K + ions across membranes. Despite their broad distribution, the physiological roles of individual members of this diverse channel family have only been thoroughly explored in eukaryotic systems, where they have critical functions in a variety of cellular processes. Recent studies have demonstrated that bacterial K + channels have integral roles in electrical signaling, information propagation, and intercellular communication. We discuss how these novel findings impact our understanding of bacterial physiology and the need to continue to explore the native roles of ion channels in microbes. Highlights: Development of novel methods have enabled detailed studies of K + channels under native conditions. Recent studies have demonstrated that channel-mediated electrical signaling is used for bacterial communication and for information storage and propagation. New structural studies revealed that several previously described bacterial transporters are nonselective ion channels.